2004
DOI: 10.1017/s0021859604003922
|View full text |Cite
|
Sign up to set email alerts
|

Dry-matter partitioning and radiation-use efficiency in cowpea cultivars (Vigna unguiculata (L.) Walp. cvs TC-9-6 and M-28-6-6) during consecutive seasonal courses in the Orinoco llanos

Abstract: SU MMARYField work on rainfed cowpea (Vigna unguiculata (L.) Walp. cvs TC-9-6 and M-28-6-6) was conducted in the Orinoco lowlands to explain the changes in dry-mass partitioning and radiation-use efficiency (RUE) as compared with other cultivars over four consecutive seasons. Growth features were assessed in early-maturing, prostrate-canopy (TC-9-6), and medium-maturing, erect-canopy (M-28-6-6) cowpeas. These cultivars were sown in consecutive middle-wet and late-wet seasons in double peak rainfall conditions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…It was observed that 25.4% of the total variance of pod and seed yield and 100% of the cause effect relationship were also explained by the first association (Fig 2). Absorption of PAR enhanced the drymatter accumulation as well as seed yield in soybean (Purcell et al, 2002;Ponte de Souza et al, 2009), maize (Lindquist et al, 2005), cowpea (San Jose et al, 2004) Results revealed that the variety Pant Mung-5 (V 1 ) may be adopted for sowing during first week of March (D 2 ) for better productivity because of its higher ability to absorb the PAR and PAR use efficiency than the other varieties and other dates of sowing tested.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…It was observed that 25.4% of the total variance of pod and seed yield and 100% of the cause effect relationship were also explained by the first association (Fig 2). Absorption of PAR enhanced the drymatter accumulation as well as seed yield in soybean (Purcell et al, 2002;Ponte de Souza et al, 2009), maize (Lindquist et al, 2005), cowpea (San Jose et al, 2004) Results revealed that the variety Pant Mung-5 (V 1 ) may be adopted for sowing during first week of March (D 2 ) for better productivity because of its higher ability to absorb the PAR and PAR use efficiency than the other varieties and other dates of sowing tested.…”
Section: Resultsmentioning
confidence: 98%
“…The mungbean as a C 3s crop has a low potentiality for grain yield. In crops, determinants of drymatter production are the absorption of solar radiation by the canopy and the efficiency with which this radiation is utilized for biomass production i.e., radiation use efficiency (Montieth, 1977;Gallagher and Biscoe, 1978 ;San Jose et al, 2004, Zhou et al, 2011Nath et al, 2012). A number of factors are responsible to the variation of estimation of radiation use efficiency (RUE).…”
Section: Introductionmentioning
confidence: 99%